Comparative Analysis of SDLC and R&D Methods in System Development: A Case Study of Integrity Zone Management System - Perdana, Adidtya; Dewi, Sri; Farhana, Nurul Ain; Febrian, Didi (Politeknik Ganesha Medan, 2025)
This paper presents a comprehensive comparative analysis of Software Development Life Cycle (SDLC) and Research and Development (R&D) methodologies in system development, with a specific focus on their application to the Integrity Zone Management Information System. Through a systematic literature review and an in-depth case study analysis, this research examines the fundamental differences, strengths, and limitations of each methodology. The study identifies key dimensions for comparison including flexibility, risk management, innovation potential, documentation requirements, and stakeholder engagement. Findings reveal that while SDLC methodologies provide structure and predictability for well-defined requirements, R&D approaches offer greater innovation capacity for exploratory projects. The Integrity Zone Management Information System case demonstrates how hybrid approaches can leverage the strengths of both methodologies and improved stakeholder satisfaction by 94%. This research contributes to the theoretical understanding of system development methodologies and provides practical guidance for selecting appropriate approaches based on project context, objectives, and constraints. The paper concludes with recommendations for practitioners and suggestions for future research in methodological integration and adaptation.